Problems of development of the modern con- ceptual apparatus of sociology - Evelkin, Georgiy M. (Journal of the Belarusian State University. Sociology, 2023)
The ideas of sociological science about the concepts that determine its status are analysed. It is noted that the substantive basis of the concepts «personality», «behaviour» and «activity» is not perceived unambiguously and is replaced by definitions that are not directly related to reality. The conscious use of concepts using symbolic language makes it possible to develop techniques and rules for studying the surrounding world, taking into account the subject of knowledge of a particular science. The concepts of «individual», «personality», «subject of activity», «object of activity», «behaviour», «activity » are considered. An attempt is made to substantiate the significance of the concepts of «personality», «behaviour», and «activity» as modern categories of sociological science. The idea is emphasised that the problems of the development of modern sociology are directly related to the clarification of its conceptual apparatus and the possibilities of its use as a tool of scientific knowledge, since a clear and unambiguous definition of concepts allows us to reveal the essence of the social processes and phenomena being studied.
Keywords: individual; personality; subject of activity; object of activity; behaviour; activity; political, economic, spiritual spheres of society